HUBUNGAN PEMBAGIAN KERJA DAN WEWENANG PERUSAHAAN DENGAN PRESTASI KERJA DI KANTOR PERTANAHAN KOTA MEDAN - gresmita yulia situmorang; prihatin lumbanraja (Universitas Sumatera Utara, 2013)
Abstract The purpose of this study is to find out the relationship between the division of job and the authority of employees toward work achievement in Section of survey, measurement and mapping at Kantor Pertanahan Kota Medan. In this study, the population are 114 in Kantor Pertanahan Kota Medan. Cencus method is used in this sudy in which consists of 42 employees in the division of survey, measurement and mapping in Kantor Pertanahan Kota Medan. The result of this study indicates that there is positive and significant relationship between the division of job and the authority of employees toward work achievement. Pearson correlation method indicates that the relationship of the division of job is stronger than the authority of employees toward work achievement. Keywords: Division of Job, Authority of Employees, and Work Achievement